The Pioneer Effect: A New Physics with a New Principle - Russell Bagdoo (New Trends in Physical Science Research Vol. 1, 2022)
Radiometric data from the Pioneer 10/11, Galileo and Ulysses spacecraft indicated an anomalous constant acceleration acting on them, directed toward the Sun, and a gradual growth of the radio signal frequency emitted by the receding transmitter. The reported odd acceleration of Pioneer 10 with a magnitude \(8.5 × 10^-10\) m/s2 can be explained by an induced gravitational interaction on the S-band signals traveling between the probe and the Earth, arising from the electromagnetic properties of the outer Solar System vacuum zero-point radiation interacting with matter. Their nature is of quantum vacuum origin, and these induced forces act in addition to ordinary gravitational forces, violating the principle of Equivalence. We suggest a new physical theory based on a new principle called “Compensation” as a thinkable explanation for the non-conventional Pioneer effect. The theory of Relation, which is an alternative to the inflationist model, postulates that our universe is made of two antagonistic but complementary structures. The principle of Compensation contradicts Relativity theory, predicts such acceleration and is for the electromagnetic spacetime metric what the principle of Equivalence is for the gravific spacetime metric.